2019
DOI: 10.14309/ajg.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Is Transient Elastography Needed for Noninvasive Assessment of High-Risk Varices? The REAL Experience

Abstract: INTRODUCTION: The Baveno VI consensus guidelines and an expanded algorithm suggest that transient elastography (TE) and platelet (PLT) count can be used to identify patients with cirrhosis who can avoid esophagogastroduodenoscopy (EGD). The primary aims of this study were to assess the ability of a simple algorithm, which uses only laboratory parameters, to predict medium/large esophageal varices (EV) in patients with hepatitis C virus (HCV) and cirrhosis from the Rete Sicilia Selezione Terapia–HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 17 publications
3
33
1
Order By: Relevance
“…Most studies that attempted to noninvasively rule out HRV, however, were retrospective and did not include an assessment of EV size [ 23 ]. Reassuringly, the diagnostic performance of the RESIST-HCV criteria was consistent with the performance reported in the recently published study [ 13 ]. Second, LSM measured by TE is useful for the assessment of HRV.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most studies that attempted to noninvasively rule out HRV, however, were retrospective and did not include an assessment of EV size [ 23 ]. Reassuringly, the diagnostic performance of the RESIST-HCV criteria was consistent with the performance reported in the recently published study [ 13 ]. Second, LSM measured by TE is useful for the assessment of HRV.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we validated the recently published RESIST-HCV criteria [ 13 ] that use only platelet count and serum albumin level to identify patients who are at low risk of HRV and can safely avoid endoscopic screening, saving time and reducing costs. This is the first validation performed in Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Augustin et al proposed that the expanded Baveno criteria (LS < 25 kPs and platelet count > 110,000/μl) may outperform the original Baveno criteria since it spares 40% of variceal screening endoscopies with a missing VNT rate of 1.6% (Augustin et al, 2017). Since, multiple studies attempted to validate these criteria with various success (Petta et al, 2018; Calvaruso et al, 2019; Dajti et al, 2019; Moctezuma-Velazquez et al, 2019; Tosetti et al, 2019a). However we must be aware that the higher SER with the application of the expanded Baveno criteria may be associated with an increased number of missed VNTs (i.e., false negative cases in the 2 × 2 diagnostic table) because the negative predictive value of the criteria is dependent on the pre-test probability of VNTs (i.e., a more severe liver disease with higher VNT rate will be associated with a lower negative predictive value of the criteria).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia may be due to hypersplenism caused by PH and an impaired immune system ( 34 36 ). Calvaruso et al ( 37 ) reported that PLT was superior to LS in predicting large EV; however, both showed low AUROCs. The study reported that these noninvasive tests did not accurately detect small EV.…”
Section: Discussionmentioning
confidence: 99%